Wavelength Division Multiplexing Passive Optical Network modeling Using Optical System Simulator - Hussain, Nahla Abdulrahman (Al-Khwarizmi Engineering Journal, 2015)
AbstractDue to the continuing demand for larger bandwidth, the optical transport becoming general in the access network. Using optical fiber technologies, the communications infrastructure becomes powerful, providing very high speeds to transfer a high capacity of data. Existing telecommunications infrastructures is currently widely used Passive Optical Network that apply Wavelength Division Multiplexing (WDM) and is awaited to play an important role in the future Internet supporting a large diversity of services and next generation networks. This paper presents a design of WDM-PON network, the simulation and analysis of transmission parameters in the Optisystem 7.0 environment for bidirectional traffic. The simulation shows the behavior of optical fiber links when the signal passes through all the components such as optical fiber, splitters, multiplexers then find a good quality of signal in all receivers. The system performance is presented through various parameters such as BER analyzer and the Eye Diagram. Keywords: Passive Optical Network (PON), Eye Height,  Bit Error Rate (BER),  Quality factor (Q).